Urban creep on the green areas and its environmental effects on the city of Baghdad - كمونة, أ.د.حيدر عبدالرزاق; سلمان العزاوي, د.وداد داود (Journal of Planner and Development, 2009)
he planning process is generally aimed at developing the city and making it meet the needs of different citizens. The green areas constitute one of the basic needs of the city and with the rapid and unusual growth in the size of cities, especially in the third world countries, which is often embodied in capitals. Which was achieved as a result of many reasons, including political, economic and social and even enshrined through some of the decisions that were issued and the city of Baghdad, but a clear example of these cities. The city and the environment are inseparable terms. The city is where people spend their lives and their daily experiences, and the environment is the center in which they live. The environment is not an area isolated from actions, aspirations and human needs. It is the sum total and the outcome of all external factors that affect the life of the organism. The environment is a complex dynamic system in which many interactive components are intertwined, and their knowledge of these components, their interactions and the relationships between man and natural resources and his developmental plans have made us realize more than ever that unless development is guided by environmental considerations, development results will be undesirable and return With few benefits or even completely fail. Therefore, we see that the countries, especially the developed ones, have given this aspect a lot of their concerns, but attention to this aspect in Iraq has been and is still below the required level and is reflected in the level of overrun on green areas and indifference to its importance in terms of climatic, aesthetic and environmental ..., by not implementing The plan is the basis for it, but it is overrun. Hence, the choice of Baghdad (the study area) and the problems mentioned previously of a population explosion and the resulting problems as well as the harsh climate that makes the green areas an urgent need to address the harsh conditions experienced by the city. As the problem was exacerbated and complicated and the inability of all the executive authorities to stop the urban encroachment on green areas and reduce abuses. The issue of land uses for urban purposes has faced serious problems in Iraqi cities, especially in Baghdad. Failures have been repeated in implementing the basic plan for the green areas due to ignoring their climatic, environmental, economic and social importance and making decisions that failed to understand the nature of this component. The absence of environmental legislation and the low environmental awareness of these institutions and society in general. Therefore, as planners, we have to recognize the fact that the environment is a moral responsibility that will be borne by all, and that any planning process must take into account the environmental aspects of achieving sustainable development that preserves the right of future generations